Efforts to Improve Student Learning Outcomes through Demonstration Methods in Fiqh Learning at MI Khoirul Huda - Munawaroh; Mutmainah (Journal of Action Research in Islamic Education, 2025)
This study aims to determine: 1) Implementation of the use of demonstration methods on hajj and umrah materials in fiqh subjects for class V students of Madrasah Ibtidaiyah Khoirul Huda in the 2023/2024 academic year. 2) To find out whether the demonstration method on hajj and umrah materials in fiqh subjects can improve the learning outcomes of class V students of Madrasah Ibtidaiyah Khoirul Huda. This research method uses Classroom Action Research (CAR). Primary data sources are taken from direct observations in the field and interviews with teachers, students and the principal of Madrasah Ibtidaiyah Khoirul Huda. The secondary sources are in the form of literature, daily grades, attendance lists, archives, reading materials, and others. Based on the results of the research and discussion, the author can conclude as follows: 1) The application of the demonstration method to the material of the hajj and umrah subject of fiqh for class V students of the Khoirul Huda Elementary School in the 2023/2024 academic year. can increase student activeness in teaching and learning activities. 2) The teacher's efforts to improve student learning outcomes in the material of the hajj and umrah subject of fiqh for class V students of the Khoirul Huda Elementary School in the 2023/2024 academic year. through the demonstration method were successful. This increase even exceeded the research target of 85%. This conclusion is supported by the results of the test carried out at the end of cycle II which increased compared to the results of the tests carried out in the pre-cycle and the end of cycle I. The results of the cycle II test showed that classical completeness reached 88% with an average student score of 75.64, which previously in the pre-cycle it was known that classical learning completeness only reached 20% with an average test score of 61.72. While in cycle I, classical learning completion reached 52% with an average value of 71. Classical learning completion between the pre-cycle range and the last implementation of cycle II increased by 34%.